NANOENKAPSULASI ASAP CAIR DALAM KITOSAN DAN MALTODEKSTRIN MENGGUNAKAN TEKNIK SPRAY DRYING - , Satrijo Saloko; , Prof. Dr. Purnama Darmadji, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Liquid smoke (LS) produced through refining process from crude coconut shell liquid smoke, and potentially as food preservative because of some chemical composition roles as antioxidative and antibacterial. However, the liquid form of LS has limited point for handling and the physicochemical properties are easy to change during storage. So that, there is a need to convert liquid to solid (powder) and protected its bioactive compound using encapsulation technique. This process is unique and has special technique, because the major proportion of LS are composed of water and acids. Therefore, the encapsulation process occurs from dispersion system that involves appropriate technique. The general objective of this research was to bring the nanoencapsulation technology of LS using chitosan (CS) and maltodextrin (MD) as encapsulants which is expected to high potency as a natural food preservative. In addition, the specific objectives were (i). to determine appropriate consentration of LS as a core and chitosan and maltodextrin as an encapsulants to get dispersion nanoparticle properties (by Nano Zetasizer and Transmission Electron Microscopy), (ii). to evaluate the optimation process of nanoencapsulation by using spray drying technique on physicochemical properties (by GC-MS), (iii). to evaluate the applications of LS nanocapsules as food preservative in model system. This research consisted of three stages namely the first stage was the determination of optimation dispersion nanoparticle processed that consisted of two experimental factors i.e. first factor was the treatment formulation which had five formulation dispersion nanoparticles (F1 = CS 0.5% in acetic acid (AA) 1%+MD 9.5%